Border policing: a history of enforcement and evasion in North America - Karibo, Holly M.; Diaz, George T. (University of Texas Press, 2020)
Introduction /Holly M. Karibo and George T. Díaz --Part I. Emerging borders : policing boundaries in the nineteenth century.Defining the acceptable bounds of deception : policing the prize game in the northeastern borderlands, 1812-1815 /Edward Martin --Dominance in an imagined border : Santos Benavides's and Santiago Vidaurri's policing of the Rio Grande /Luis Alberto García --A border without guards : First Nations and the enforcement of national space /Benjamin Hoy --Part II: Solidifying States, Testing Boundaries.To protect and police : Mexican consuls in the American borderlands at the turn of the twentieth century /María de Jesús Duarte --Enforcing US immigration laws at the US-Canada border, 1891-1940 : the view from Detroit /Thomas A. Klug --The roots of the border patrol : line riders and the bureaucratization of US-Mexican border policing, 1894-1924 /James Dupree --Home guard : state-sponsored vigilantism and violence in the Texas-Mexico borderlands /Miguel A. Levario --Part III: Building and resisting a Prohibition apparatus.Policing peyote country in the early twentieth century /Lisa D. Barnett --Skirting the law : female liquor smugglers and sellers and policing through Prohibition along the Rio Grande /Carolina Monsivais --Building a villain/hero binary : public rhetoric, smuggling, and enforcement in the postwar borderlands /Holly M. Karibo --Part IV: Expanding state authority and its challenges.Diversity and the border patrol : race and gender in immigration enforcement along the US-Mexico Border /Jensen Branscombe --Refusing borders : Haudenosaunee resistance, tobacco, and settler-colonial borderlands /Devin Clancy and Tyler Chartrand --Border surge : drug trafficking and escalating police power on the Rio Grande /Santiago Ivan Guerra --Bordering reality : dramatizing policing the North American borderlands in reality television /Anita Huizar-Hernández.